Co-cultures of Glioma Stem Cells and Primary Neurons, Astrocytes, Microglia, and Endothelial Cells for Investigation of Intercellular Communication in the Brain - Wei, Zhiyun; Kale, Shubham; El Fatimy, Rachid; Rabinovsky, Rosalia; Krichevsky, Anna M. (Frontiers in Neuroscience, 2019)
Intercellular communication within complex biological and pathological systems via extracellular vesicles (EV) and secreted factors is a highly attractive area of research. However, cell models enabling investigation of such communication in vitro are limited. Commonly utilized is the supplementation of super physiologically concentrated EVs or other extracellular factors to the recipient cell cultures. This approach requires purification of the secreted complexes and is confounded by the contamination of media components. Two-chamber co-cultures of donor and recipient cells separated by a pore membrane may represent a more physiological and better-controlled system for the investigation of intercellular communication. Yet, distinct culture conditions for different neural cell types often make them incompatible for co-culturing. Here we optimized short-term co-cultures of patient-derived low-passage glioma-initiating stem cells with normal cells of the brain microenvironment, such as primary neurons, astrocytes, microglia, and brain endothelial cells. We demonstrate the culture compatibility of these cell types and internalization of glioma-derived extracellular RNA by the normal recipient cells. The presented protocols are valuable for the investigation of intercellular communication between glioma brain tumor and cells of its microenvironment, including but not limited to the EVs-mediated communication.